PENGGUNAAN PERHITUNGAN MANUAL NILAI BASE EXCESS PADA KEADAAN ASIDOSIS - Mardiana Mardiana; Chairlan Chairlan; Siri Rismini; Elok Ekawati (Poltekkes Kemenkes Jakarta III, 2013)
Acidemia is the acidity of the blood characterized by blood pH less than 7.34. The process is known as acidosis. Primary metabolic acidosis characterized by decreased levels of bicarbonate in the blood. Metabolic acidosis can be overcome by administering sodium bicarbonate (NaHCO3). Correction of acid-base can be done by calculating the dose NaHCO3 obtained from body weight, dose and base excess values. Base excess value itself can be obtained in two ways: directly from blood gas analyzers and manual calculations. The results showed the average value of BE blood gas analyzer (BGA) tool is -5.8467, while the BE manual calculation is -5.5217. From the statistical test obtained Signifiancy numbers 0.656, meaning there is no significant difference between the BE values of BGA and manual calculations. It can be concluded that the value of BE obtained from manual calculation can be bicarbonate correction if the reference to blood gas analyzers do not include the value of BE.